TEACHERS' PERFORMANCE IN TEACHING SCIENCE USING ENGLISH IN BILINGUAL CLASSES : A Qualitative Study on 7th Grade of Non English Teacher of One State Junior High School in Cimahi - Lussy Anggraeni, - (2011)
The study entitled Teachers' Performance in Teaching Science Using English in Blingual Classes aims at seeking how science teachers use English to teach Science (kinds of teacher's talk, teacher's time of using English) and the difficulties encountered by those teachers while teaching Science using English in bilingual classes. The study took place in one state Junior High school in Cimahi. The Physics and Biology teachers were chosen as respondents. This study used descriptive qualitative method and the data were gained through observations, video recording and interviews. The result of this study shows that there are seven categories of teacher's talk which are grouped into two sub categories namely indirect influence: dealing with feeling, praising or encouraging, using ideas of students, and asking questions, and direct influence; giving information, giving direction, and criticizing student behavior. The result also shows that there are eight stages in which teachers use English to teach Science in bilingual classes: opening the lesson, giving explanation, asking students, giving instruction, answering students' questions, giving compliment, summarizing material and closing the lesson. Moreover, this study indicates some reasons why Science teachers use English when they use Science terms. In addition, this study discovers some difficulties encountered by science teachers in teaching Science using English in bilingual classes. There are; (1) how to deliver the material to students where English as classroom language, (2) how to make students comprehend in English by choosing proper vocabulary, and (3) how to formulate the questions.